2020
DOI: 10.3390/molecules25112477
|View full text |Cite
|
Sign up to set email alerts
|

The Targeted Impact of Flavones on Obesity-Induced Inflammation and the Potential Synergistic Role in Cancer and the Gut Microbiota

Abstract: Obesity is an inflammatory disease that is approaching pandemic levels, affecting nearly 30% of the world’s total population. Obesity increases the risk of diabetes, cardiovascular disorders, and cancer, consequentially impacting the quality of life and imposing a serious socioeconomic burden. Hence, reducing obesity and related life-threatening conditions has become a paramount health challenge. The chronic systemic inflammation characteristic of obesity promotes adipose tissue remodeling and metabolic change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 229 publications
(265 reference statements)
0
22
0
Order By: Relevance
“…A metagenomic analysis indicated that the tea extracts changed the gut microbiota’s composition [ 428 ]. In the same way also flavones ‘effects on obesity has been linked to gut microbiota modifications [ 338 ]. Oral hydroxysafflor yellow A (HSYA) reversed the HFD-induced gut microbiota dysbiosis and reduced the obese phenotype [ 429 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A metagenomic analysis indicated that the tea extracts changed the gut microbiota’s composition [ 428 ]. In the same way also flavones ‘effects on obesity has been linked to gut microbiota modifications [ 338 ]. Oral hydroxysafflor yellow A (HSYA) reversed the HFD-induced gut microbiota dysbiosis and reduced the obese phenotype [ 429 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the richest sources of flavones are parsley, celery, peppermint, and sage, which predominantly contain apigenin and luteolin as well as maize and citrus fruits. In general, flavones are found as glucosides in citrus fruits, vegetables, herbs and grains and although they represent a small fraction of the total flavonoid intake, they have shown health effects and anti-obesity properties [ 338 , 339 ]. As it is going to described latter, most of the studies that investigate the beneficial effects of flavones use them as aglycone and a scarce number of approaches deepen on the effects of flavones when consumed within the whole food and a feasible doses or in combination with other bioactive compounds.…”
Section: Flavonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, reducing obesity and associated life-threatening diseases has become an emerging area of health sciences. In this Special Issue, Sudhakaran and Doseff have contributed to a comprehensive review of the impact of dietary flavones on obesity-induced inflammation [ 27 ]. The common flavones are luteolin, apigenin, chrysin, baicalin, acacetin, orientin, and apigenin, which could be found in food sources such as citrus fruits, vegetables, herbs, and grains.…”
Section: The Relevance Of Flavonoids In Obesity Preventionmentioning
confidence: 99%
“…This is largely mediated by gut microbiota as it increases adiposity and fatty acid metabolism. Further, intestinal microbes modify flavonoids by glucosidation, dihydroxylation, and decarboxylation converting them into monomers, which can be more absorbable in the intestine [211]. To add, flavonoids isolated from mulberry leaves ameliorate lipid dysmetabolism in the high fat diet (HFD)-fed mice.…”
Section: Flavonoids and Dietary Intakementioning
confidence: 99%